Insights in the Antimicrobial Potential of the Natural Nisin Variant Nisin H - Reiners, Jens; Lagedroste, Marcel; Gottstein, Julia; Adeniyi, Emmanuel T.; Kalscheuer, Rainer; Poschmann, Gereon; Stühler, Kai; Smits, Sander H. J.; Schmitt, Lutz (Frontiers in Microbiology, 2020)
Lantibiotics are a growing class of antimicrobial peptides, which possess antimicrobial activity against mainly Gram-positive bacteria including the highly resistant strains such as methicillin- resistant Staphylococcus aureus or vancomycin-resistant enterococci. In the last decades numerous lantibiotics were discovered in natural habitats or designed with bioengineering tools. In this study, we present an insight in the antimicrobial potential of the natural occurring lantibiotic nisin H from Streptococcus hyointestinalis as well as the variant nisin H F1I. We determined the yield of the heterologously expressed peptide and quantified the cleavage efficiency employing the nisin protease NisP. Furthermore, we analyzed the effect on the modification via mass spectrometry analysis. With standardized growth inhibition assays we benchmarked the activity of pure nisin H and the variant nisin H F1I, and their influence on the activity of the nisin immunity proteins NisI and NisFEG from Lactococcus lactis and the nisin resistance proteins SaNSR and SaNsrFP from Streptococcus agalactiae COH1. We further checked the antibacterial activity against clinical isolates of Staphylococcus aureus, Enterococcus faecium and Enterococcus faecalis via microdilution method. In summary, nisin H and the nisin H F1I variant possessed better antimicrobial potency than the natural nisin A.